Framework for utilizing computational devices within simulation - Miroslav Mintál (Acta Informatica Pragensia)
Nowadays there exist several frameworks to utilize a computation power of graphics cards and other computational devices such as FPGA, ARM and multi-core processors. The best known are either low-level and need a lot of controlling code or are bounded only to special graphic cards. Furthermore there exist more specialized frameworks, mainly aimed to the mathematic field. Described framework is adjusted to use in a multi-agent simulations. Here it provides an option to accelerate computations when preparing simulation and mainly to accelerate a computation of simulation itself.